DAPUR RUMAH TINGGAL YANG ERGONOMIS BAGI PENGHUNINYA - Soewarno, Aik (Jurnal Natah, 2012)
Kitchen is one of room that should be presented in a house. Kitchen is not just for the sake of as a place to prepare a food, but also as recreation, communication for the family. Cooking is routine activity; working in kitchen is completed from morning till night, starting from preparing breakfast, lunch till dinner. This activity is predicted taking time around eight hours. Cooking activity is categorized as a half hard working. Activity in kitchen is a tired work. Attitude of force work caused by the use of tools that is not appropriate to ergonomics requirement, will effect to the body health. To overcome those problem require completed the effort of improvement through adjusting the height of working area by heightening the working floor accordance with the measurement of worker’s anthropometry. The height of working area is 10 cm under the height of worker’s elbow. This improvement expected could change the work attitude that is not ergonomic, become ergonomic. Through the use of pre-test and post-test group design, this study had been conducted by sampling of 21 subjects and selected by plainly random technique. Work throb pulse is measured by the method of ten throbs and subjective complaint on the system of muscle skeleton, and encoded by Nordic Body Map and force attitude proved by encoding the number of worker’s anthropometry measurement and the photo document of work tools dimension. The statistical test that had been used is “student t-test”. The result of the study shows that the improvement of work attitude reduce the complaint on the system of muscle skeleton as 23,96 % (p < 0,05) and diminish the work throb pulse as 23,13% (p> 0,05). By this study can be concluded that through the improvement of work attitude, could reduce the workload as additional load. It means that by utilizing the ergonomically kitchen will acquire the comfortable to the occupant.
Keywords: anthropometry, ergonomic, and work attitude.